Ultra high performance concrete and C-FRP tension Re-bars: A unique combinations of materials for slabs subjected to low-velocity drop impact loading - Anas, S. M.; Alam, Mehtab; Isleem, Haytham F.; Najm, Hadee Mohammed; Sabri, Mohanad Muayad Sabri (Frontiers in Materials, 2022)
In this research work, different combinations of normal strength concrete (NSC), ultra-high-performance concrete (UHPC), and steel fiber-reinforced UHPC (SFR-UHPC) concrete with re-bars of conventional steel and of carbon fiber-reinforced polymer (C-FRP) are used in a two-way square slab of size 1000mm x 1000mm x 75mm subjected to 2500mm free-fall impact loading. Experimental arrangement consisting of 105kg dropping weight with the circular flat impacting face of 40mm diameter used for carrying out impact test is modeled using a high-fidelity physics-based finite element computer code, ABAQUS/Explicit-v.6.15. After validating the experimental results of the NSC slab with steel bars, analyses are extended by replacing NSC and steel bars with UHPC/SFR-UHPC and C-FRP bars, respectively, under the same dropping weight. Only the remote face (tension face) of the slabs is provided with the re-bars. Widely employed and available with the ABAQUS, the Concrete Damage Plasticity model with strain-rate effects has been entrusted for simulating the concrete plastic response. Re-bars of steel are idealized with the Johnson-Cook plasticity damage model. C-FRP re-bars are defined with the classical plasticity model following the elastic-plastic constitutive laws. The impact responses of the slabs consisting of NSC/UHPC/SFR-UHPC concrete with re-bars of steel, and C-FRP combinations considered are discussed and compared. Slabs made of UHPC/SFR-UHPC concrete with the C-FRP re-bars are found to offer a promising combination of materials to withstand low-velocity impact load with little damage and extraordinary impact performance.